(untitled) (Research, Society and Development, 2020)
Pepper extract (PE, 5 g capsaicin/kg PE) was added to the feed of the sheep during the lactation period (Day 75-93) to maintain production, improve milk quality, and preserve their health. The groups were: T0, control, (without PE); T200 (200 mg PE/kg concentrate) and T400 (400 mg PE/kg concentrate). The reduction in milk production (L) was smaller in the T400 ewes on days 0 to 18 and 14 to 18 than in the T0 group. Feed conversion was lower in sheep in groups T200 and T400 than in group T0. The interaction between the treatment and the day for protein, lactose and total milk totals was greater in ewes that consumed PE on day 18. The somatic cell counts in milk were lower in the T400 ewes. The levels of total protein and globulin were the highest in the blood of animals in the T400 group. There were lower levels of reactive oxygen species and lipoperoxidation in the serum and milk of animals in groups T200 and T400. On the 18th day, the serum of sheep that consumed PE increased levels of non-protein thiols and superoxide dismutase activities. The inclusion of PE (400 mg/kg) containing capsaicin in sheep concentrate in the middle of lactation (after the peak of lactation) minimized the reduction in milk production during the experiment and improved the quality of the milk, as well as stimulated an antioxidant response systemic.